The Effect of Nigella Sativa Linn (Kalajira) Extract on Gentamicin- Induced Nephrotoxicity in Experimental Rats (Journal of Dhaka Medical College, 2017)
The pathogenesis of gentamicin-induced nephrotoxicity has shown to generate oxygen free radicals. Several free radical scavengers are well recognized to ameliorate the nephrotoxicity. The seeds and oil of nigella sativa were reported to possess strong antioxidant properties and was effective against disease and chemically-induced hepatotoxicity and nephrotoxicity.The experiments were carried out in two parts, Experiment I and Experiment II, on a total of 35 rats of 8-12 weeks old and weighing between 200 and 230g. Nephrotoxicity and amelioration of nephrotoxicity was evaluated by measurement of concentrations of serum creatinine. The rats were induced nephrotoxicity by subcutaneous injection of gentamicin 100mg/kg/day for 9 days and were sacrificed on 10th day. The results indicated that gentamicin treatment caused marked renal tubular damage significant increase (P